(untitled) (Journal of Biomedical Investigation, 2025)
Background: Physical inactivity is a major public health concern and a significant risk factor for non-communicable diseases, particularly among women in low- and middle-income countries where sociocultural and environmental demands may limit physical activity participation. Aim: This study assessed the levels of physical activity, perceived benefits, and perceived barriers to physical activity among adult women residing in Nnewi, Anambra State, Nigeria. Materials and methods: A cross-sectional study design involving 400 adult women selected from the four quarters of Nnewi was adopted. The International Physical Activity Questionnaire-Short Form (IPAQ-SF) assessed physical activity level, while the Exercise Benefits and Barriers Scale (EBBS) assessed perceived benefits and barriers. Data was summarized using frequency counts, charts, mean and standard deviation while the Kruskal-Wallis test was used for analysis at the <0.05 level of significance. Results: The mean age of participants was 30.77±11.15 years. Participants demonstrated high perceived exercise benefits (mean score 89.12±20.05) and moderate perceived barriers (36.10±9.15). Modal reported walking and moderate physical activity duration was less than 30 minutes to 1 hour. Respondents who reported the highest sitting period also recorded the highest benefits (p=0.003) yet more barriers to walking (p<0.001). Conclusions: Women in Nnewi exhibit favourable perceptions of exercise benefits but relatively low engagement in vigorous physical activity, with notable barriers linked to sedentary behaviour and daily responsibilities. Targeted interventions addressing contextual barriers and promoting active lifestyles are recommended to improve physical activity participation among women in this population.